2018
DOI: 10.3389/fenvs.2018.00062
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Dissolved Organic Phosphorus in Temperate Lakes

Abstract: Freshwater aquatic systems are biogeochemical hotspots, with heterotrophic bacteria rapidly cycling the compounds that pass through them. P is a key nutrient that controls primary production in many freshwater ecosystems and is important for understanding eutrophication in lakes. Previous work has often focused on the dynamics of inorganic phosphorus and its impact on primary production, however, the role of nutrients bound in more complex organic forms (such as dissolved organic phosphorus, DOP) in supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Across space, we observed that DOC and nutrients were tightly correlated, with organically bound nutrients comprising approximately 38% of TP and 67% of TN, and few differences in nutrient stoichiometry between regions. Our results build on past spatial studies that have demonstrated tight regional coupling between DOC concentration and nutrient concentration (e.g., Perakis and Hedin 2007;Corman et al 2018;Thompson and Cotner 2018;Isles 2020). However, our results also show that the ratio of TP : DOC decreased Fig 4 . Estimates of whole-lake peak summer average photosynthetic potential for 28 study lakes over the period 1994-2012 in the Adirondacks (data from Leach et al 2018b).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Across space, we observed that DOC and nutrients were tightly correlated, with organically bound nutrients comprising approximately 38% of TP and 67% of TN, and few differences in nutrient stoichiometry between regions. Our results build on past spatial studies that have demonstrated tight regional coupling between DOC concentration and nutrient concentration (e.g., Perakis and Hedin 2007;Corman et al 2018;Thompson and Cotner 2018;Isles 2020). However, our results also show that the ratio of TP : DOC decreased Fig 4 . Estimates of whole-lake peak summer average photosynthetic potential for 28 study lakes over the period 1994-2012 in the Adirondacks (data from Leach et al 2018b).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, space for time substitutions (Pickett 1989), experiments, and modeling have been implemented to predict the long-term effects of lake browning (Ask et al 2009;Finstad et al 2014;Kelly et al 2014;Bergström and Karlsson 2019). Spatially, studies have found constant nutrient stoichiometry across a wide range in DOC concentrations (Perakis and Hedin 2007;Corman et al 2018;Thompson and Cotner 2018). However, temporal trends may not be consistent with spatial patterns (e.g., Isles et al 2018), which may indicate that long-term trends in DOM quality (e.g., P : DOC, N : DOC, a d : DOC, and P : a d or N : a d ) are not well understood.…”
mentioning
confidence: 99%
“…Despite their ecological importance from fresh to salty habitats, nutrients (N and P) bound to organic material have to date caught comparably less attention 41 44 . Focusing on these compounds may be especially important for boreal freshwaters and coastal systems, where overall organic compounds (C, N, P) are systematically increasing, and additionally more bioavailable than previously thought 13 , 21 , 43 46 . If only measuring total N, P and TN:TP ratios as indicators of the ecosystem’s trophic state, as well as total C or dissolved organic C (DOC) as indicators for the organic matter runoff or browning, our study would not have succeeded in detecting any of the observed strong trends in riverine loads to the coast.…”
Section: Resultsmentioning
confidence: 99%
“…The stoichiometry of DOM to nutrients plays a crucial role in regulating nutrient cycling (Berggren et al 2015;Stutter et al 2018;Yates et al 2019). The DON and DOP contributions to the DOM pool are dependent on its source and composition (Pisani et al 2020;Yates et al 2019) and have been shown to be positively correlated to DOM bioavailability (Jansson et al 2012;Pisani et al 2017;Thompson and Cotner 2018). The amount of bioavailable material can range from 10 to 70% of riverine DON (Pisani et al 2017) and 0 to 90% of DOP (Li and Brett 2013) with quantities dependant on inputs and sources of terrestrial runoff and photodegradation processes (Moran and Zepp 1997).…”
Section: The Chemical Composition Of the Dom Pool Can Modify Nutrient Cyclesmentioning
confidence: 99%